(De) Constructing The Linguistic Identity Of Undergraduate Level English As Second Language Learners: Revisiting The Language Identities Urdu And English (Journal of Namibian Studies : History Politics Culture, 2023)
This study investigates the realm of linguistic identity among undergraduate English as a Second Language (ESL) learners, focusing on the dynamic interplay between Urdu and English. Employing both quantitative methods and an interpretative approach rooted in the post-positivist paradigm, it aims to unravel the construction and deconstruction of linguistic identities within the framework of the national curriculum. The research centers around undergraduate students at Habib University, reflecting a diverse cross-section of ESL learners grappling with the complexities of Urdu and English dictated by the Higher Education Commission (HEC) guidelines. Using quota sampling, 400 students were recruited, ensuring representation across various academic disciplines. The study gathered data through a 21-item Linguistic Identity instrument, revealing nuanced identities. ESL learners displayed a preference for English in academic contexts while maintaining a strong affiliation with Urdu in terms of social identity and cultural significance. The research underscores the significance of acknowledging and preserving linguistic identities, championing linguistic diversity, and deepening our comprehension of the relationship between language, culture, and social identity in education.